A New Shunt Capacitor-Commutated Converter for Reducing Commutation Failure Probability of HVDC Transmission and Converter Transformer Noise - Hao Zhang; Sijia Hu; Longfu Luo; Jinjie Lin; Liang Zhao; Zhiwen Zhang (IEEE Access)
The HVDC transmission system with a line-commutated converter is prone to commutation failure when connected to a weak AC grid and has disadvantages such as a large footprint of AC filters and high noise from the converter transformer. This paper presents a shunt capacitor-commutated converter (SCCC) without AC filters, using a constant extinction voltage-time area (VTA) control to enhance the performance of the inverter station. First, the topology and the mathematical model of the SCCC are established, with its commutation and frequency characteristics analyzed. Second, the minimum extinction VTA criterion for preventing commutation failure is proposed, revealing how various parameters affect VTA and the mechanism by which the SCCC reduces commutation failure probability. Furthermore, a constant extinction VTA control strategy is designed for the SCCC-based inverter. Then, the reactive power and harmonic characteristics of the SCCC are analyzed. A selection method for the SC is proposed to meet the inverter’s requirements for unit power factor operation and filtering. Simulations in PSCAD/EMTDC and experimental results from a scaled-down rectifier prototype demonstrate that the SCCC and the proposed control strategy effectively reduce commutation failure probability and converter transformer noise.